2018
DOI: 10.3390/su10041238
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Low-Carbon Investment Decisions in an Emission Dependent Supply Chain under a Carbon Labelling Scheme

Abstract: Abstract:A low-carbon policy attracts the interests of businesses, consumers, and policy makers. The purpose of this paper is to investigate how a carbon labelling scheme could be integrated into operational decision-making for manufacturers and retailers. Three game theoretic models of a supply chain with one manufacturer and one retailer are built to investigate a manufacturer and retailer's pricing and investment decision for products with different initial carbon footprints considering consumer environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Xia and He [31] concluded that consumers' low-carbon awareness was to enhance consumer utility and decrease the profits of supply chain firms without regulation. Cheng et al [32] studied how a carbon-labeling scheme could be integrated into operational decision-making for manufacturers and retailers. Reference [32] shows that a carbon-labeling scheme can significantly reduce the overall carbon emission supply chain and have an initially negative impact on the manufacturer and retailer's profits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia and He [31] concluded that consumers' low-carbon awareness was to enhance consumer utility and decrease the profits of supply chain firms without regulation. Cheng et al [32] studied how a carbon-labeling scheme could be integrated into operational decision-making for manufacturers and retailers. Reference [32] shows that a carbon-labeling scheme can significantly reduce the overall carbon emission supply chain and have an initially negative impact on the manufacturer and retailer's profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheng et al [32] studied how a carbon-labeling scheme could be integrated into operational decision-making for manufacturers and retailers. Reference [32] shows that a carbon-labeling scheme can significantly reduce the overall carbon emission supply chain and have an initially negative impact on the manufacturer and retailer's profits. Zhang et al [33] study the impact of consumer environmental awareness on order quantities and channel coordination within a one-manufacturer and one-retailer supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incorporating the competition between the two rival manufacturers in the demand function, Chen et al [33] studied optimal pricing and carbon reduction policies. By considering consumer environmental awareness, Cheng et al [9] built a game theoretic model of a supply chain with one manufacturer and one retailer to investigate the manufacturer's and retailer's pricing and investment decisions for products with different initial carbon footprints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As effective choices to curb carbon emissions and mitigate greenhouse effects, carbon cap-and-trade [5,6], carbon tax [7,8], and carbon labelling [9] have all been adopted by both governments and firms. In particular, the cap-and-trade regulation has proven to be an effective way to achieve emission reduction goals [10].…”
Section: Introductionmentioning
confidence: 99%
“…e idea of carbon label is used to identify the sustainability level of a product. For instance, Walmart has requested its 100,000 suppliers to complete the carbon footprint verification and labeled their products with colors according to the carbon footprints [8].…”
Section: Introductionmentioning
confidence: 99%